Sentiment and Toxicity Analysis of Digital Content Using Perspective, Vader, and TextBlob: Tourism and Birdwatching - Singgalen, Yerik Afrianto (STMIK Budi Darma, 2024)
This research investigates the impact of digital content on specialized tourism activities, focusing on birdwatching, using tools such as Communalytic and RapidMiner. By analyzing 1,021 posts, the study reveals an average toxicity score of 0.13839, with VADER identifying 32.78% negative sentiment and TextBlob identifying 17.07% negative sentiment. Despite these negative interactions, over 50% of the posts convey positive sentiment, highlighting the potential for digital content to foster a supportive and engaging community. The findings underscore the urgent need to address toxicity to maintain a positive online environment, crucial for enhancing educational outreach and participant engagement. This research emphasizes the critical and immediate role of digital platforms, analyzed through Communalytic and RapidMiner, in promoting environmental awareness and conservation, thereby driving the growth and sustainability of niche tourism sectors such as birdwatching. Prompt action is essential to leverage these insights to benefit the environment and local economies.